Effect of Lesion Size in the Diagnosis of Hepatic Hemangioma with Tc-99m Erythrocyte Scintigraphy - Balci, Tansel Ansal; Koc, Zehra Pinar; Demirel, Bedriye Busra (Derman Medical Publ, 2012)
Aim: Diagnosis of the hepatic hemangiomas is sometimes difficult by means of computed tomography (CT) or ultrasound (USG). This kind of lesions can be accurately identified by Tc-99m labeled erythrocyte -red blood cell (RBC) imaging. However there are controversial results about small lesions (< 1.5 cm). Aim of this study is to evaluate the effect of lesion size in the diagnosis of liver hemangioma by using Tc-99m labeled RBC scintigraphy. Material and Method: Forty-two patients who had liver lesions with the suspicion of hemangioma were retrospectively evaluated. Tc-99m RBC scintigraphy results of the patients were compared with 3-24 months clinical or USG follow-up or morphological imaging methods (dynamic computerized tomography or magnetic resonance imaging (MRI)). Results: Twenty seven of 42 patients had follow-up and their diagnosis was confirmed. Sensitivity, specificity, accuracy, positive and negative predictive value of Tc-99m RBC scintigraphy according to follow up results were 92%, 66%, 89%, 96% and 50%, respectively. Two false negative lesions were smaller than 1.5 cm (10 mm, 13 mm). One of the 3 patients with small lesion who came for followup had true positive result. Existence of small lesions in the study made the specificity and negative predictive value decreased. Discussion: Although small sized (< 1.5 cm) hemangiomas sometimes can also be visualized with Tc-99m RBC scintigraphy, this technique is very sensitive especially for large lesions.
Tc-99m eritrosit sintigrafisinde lezyon boyutunun hepatik hemanjioma tanısına etkisi
Keywords: Liver Hemangioma; Scintigraphy; Tc-99m Labeled Erythrocyte; Lesion Size; Radionuclide Imaging